The Influence of Marketing Mix and Hospital Image on Inpatient Revisit Interest at Dr. Rubini Regional General Hospital, Mempawah Regency - Maura Zettira Shabrina; Rohendi Rohendi; Yen Efawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The marketing mix is one of the strategies used to disseminate information, introduce products and services, and encourage consumers to make repeat purchases. Image plays an important role in determining the success of an institution, including hospitals. Patients’ intention to make repeat visits is influenced by several factors, including marketing strategies and a positive hospital image. This study aims to analyze the effect of the marketing mix and hospital image on the revisit intention of inpatients at dr. Rubini Regional Public Hospital, Mempawah Regency. This research employed a mixed-methods approach with an explanatory sequential design. The study began with a quantitative phase involving 100 respondents, complemented by qualitative data from interviews with six informants. The results show that five elements of the marketing mix—product, place, people, process, and physical evidence—as well as hospital image have a significant effect on patients’ revisit intention, whereas two elements of the marketing mix, promotion and price, do not have a significant effect. However, taken together, all nine variables have a significant effect on patients’ revisit intention. The qualitative findings support the importance of the marketing mix and hospital image for inpatients’ revisit intention.